The Impact of Endovascular Repair of Ruptured Abdominal Aortic Aneurysm on the Gastrointestinal and Renal Function - R. R. Makar; S. A. Badger; M. E. O’Donnell; C. V. Soong; L. L. Lau; I. S. Young; R. J. Hannon; B. Lee (International Journal of Vascular Medicine)
Introduction. Systemic effects of ruptured abdominal aortic aneurysm (rAAA) may be altered by the mode of surgery. This study aimed to determine systemic effects of endovascular aneurysm repair (EVAR) compared to open repair (OR). Patients and Methods. Consecutive patients with rAAA were repaired by OR or EVAR according to computerised tomographic (CT) findings. Renal function was monitored by estimated glomerular filtration rate (eGFR), serum urea and creatinine, and urinary albumin creatinine ratio (ACR). Hepatic function was assessed postoperatively for 5 days. Intestinal function was determined by the paracetamol absorption test. Intestinal permeability was assessed by urinary lactulose/mannitol ratio. Results. 30 rAAA patients were included. Fourteen had eEVAR and sixteen eOR. Serum urea were higher in eOR, while creatinine was similar between groups. Hepatic function showed no intergroup difference. Paracetamol absorption was increased in eEVAR group at day 3 compared to day 1 (P=0.03), with no similar result in eOR (P=0.24). Peak lactulose/mannitol ratio was higher in eOR (P=0.03), with higher urinary L/M ratio in eOR at day 3 (P=0.02). Clinical intestinal function returned quicker in eEVAR (P=0.02). Conclusion. EVAR attenuated the organ dysfunction compared to open repair. However, a larger comparative trial would be required to validate this. The clinical trial is registered with reference number EUDRACT: 2013-003373-12.